Comparison Of Donor Site Morbidity of Suprafasicial & Sub-Fascial Radial Forearm Flap in Maxillofacial Soft Tissue Defect Reconstruction - Md. Saiful Azam, Md. Ahsan Habib, Md. Shahidul Islam, Mohamad Sayeem Rahman Bhuiyan, Abu Hena Helal Uddin Ahmed (South Eastern European Journal of Public Health, 2025)
Background: The most important goal of reconstructive surgery in head and neck cancer patients is the optimal restoration of function & morphology. The FRFF is a very reliable flap which can restore function in the head and neck very well. However, the donor site morbidity after harvesting the flap is another important issue. Objective: To evaluate the donor site morbidity in oral cancer patients after reconstruction using a free radial forearm flap. Methods: Fasciocutaneous flaps were raised under a tourniquet in a conventional subfascial or suprafascial manner about 2 cm proximal to the wrist skin fold after performing Allens test. The superficial radial nerve and branches of the lateral antecubital nerve were preserved. The cephalic vein & vanae comitans was used as donor vein. The donor defect was closed with a split skin graft taken from the upper thigh at the same settings. In order to aid healing the arm was immobilized for 7 days in a dorsal hand to- upper-arm splint with a pressure dressing of a parafin gauze and foam. Results: 40 patients underwent reconstruction of maxillofacial soft tissue defects by RFFF. There was 100% complete graft take in Suprafascial technique but in Subfascial technique, 2 patients had partial skin loss. In Suprafascial Radial forearm technique there was no tendon exposure but in Sub-fascial technique there was 2 cases of tendon exposure. Considering the pain and numbness, 3 patient’s complaints pain and 5 patients complaints of numbness of the superficial radial nerve in Suprafascial Radial forearm technique but in Sub-fascial technique 5 patients complaints pain and 4 patients complaints of numbness of the superficial radial nerve. Conclusion: Suprafascial harvest of the RFFF decreases the risk of postoperative morbidity at donar site and it can be considered over the traditional subfascial harvest technique due to its superior donor site outcomes.